A modified Newton method for a quadratic vector equation arising in markovian binary trees - Deng, Liang-Jian; He, Jun; Huang, Ting-Zhu (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We prove the existence of solution for the quadratic vector equation arising in Markovian binary trees. A modified Newton method for finding the minimal solution of the equation is presented. The monotone convergence of the modified Newton method is proved. Numerical experiments show the efficiency of our method.